From Labour Migrant to Stay-at-Home Mother? Childcare and Return to Work among Migrant Mothers from the EU Accession Countries in Ireland. (October 2018) - Röder, Antje; Ward, Mark; Frese, Carmen-Adriana
Previous research on the labour market integration of migrants from EU Accession countries has primarily viewed migrants as individual economic actors, despite their increasing role in family formation. In this contribution, mothers' return to work after birth is analysed using data from the Irish childhood prospective cohort study Growing Up in Ireland . Families from the Accession countries appear to have little access to non-parental childcare or the support of extended family, which is an important resource for their Irish peers. Fewer EU Accession mothers return to paid work at the end of maternity leave, and are more likely to juggle work and childcare without support. Structural reasons as well as preferences are considered as potential explanations to develop a better understanding of how migrant status impacts on work and childcare decisions.